Development of Xander Resistance Training Exercise Model for Petanque Sports Branch at Student Level - Muhammad Nur Fajar Alis; Setyo Harmono; Budiman Agung Pratama; Boy Indrayana (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
This research aims to investigate the dynamic growth and development of the sport of petanque in Indonesia, specifically focusing on the progress witnessed during the 2011 SEA Games. Notably, the establishment of the Federation of Petanque Sports Indonesia (FOPI) marked a significant turning point, leading to rapid progress facilitated by various universities and extensive community involvement. In addition, this study emphasizes the importance of physical condition, accuracy, and mastery of basic techniques such as Pointing and Shooting to achieve success in the sport of petanque. To further improve the physical condition of petanque athletes, this research implements the Training Resistance Xander (TRX) training model, This research is a Research & Development (R&D) study with qualitative methods. The results showed the implementation of this model demonstrated a positive impact on the athletes' physical condition, highlighting its efficacy as a comprehensive training solution. This research highlights the holistic approach required for sports development, emphasizing the need for customized training models to optimize athletic performance.